Juridical Study of the Supervisory Authority over the Implementation of Nagari Customs and Culture by Traditional Nagari Communities in West Sumatra Province - Pebrihariati. R, Sanidjar; Desmal Fajri; Oksidelfa Yanto (Faculty of Law, Universitas Pekalongan, 2025)
In Article 18B paragraph (2) of the Amendment to the 1945 Constitution, it is stated that